The works of Richard Savage, Esq., son of the Earl Rivers : with an account of the life and writings of the author / by Samuel Johnson, LL.D. - Savage, Richard, -1743. (Tufts University. Tisch Library., 2015)
Volume 2 of 2; A new edition.; 1 online resource (2 volumes); Title vignette signed: H. Gravelot inv., Isaac Taylor sculp.; Electronic reproduction. Medford, MA : Tisch Library, Tufts University, 2015. Scanned by the Boston Library Consortium/Open Content Alliance as part of the BLC OCA Digitization Project from a copy at the Tisch Library, Tufts University.; Indexed in: English Short Title Catalog,T139156